2014
DOI: 10.1111/sdi.12196
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Chronic Kidney Disease: A Scoping Review

Abstract: There is increasing international attention in efforts to integrate palliative care principles, including pain and symptom management, into the care of patients with advanced chronic kidney disease (CKD). The purpose of this scoping review was to determine the extent, range, and nature of research activity around pain in CKD with the goal of (i) identifying gaps in current research knowledge; (ii) guiding future research; and (iii) creating a rich database of literature to serve as a foundation of more detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
125
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 173 publications
(253 reference statements)
1
125
0
10
Order By: Relevance
“…Dialysis patients experience a high symptom burden for years, similar to that of patients with terminal cancer receiving palliative care (41,42), and symptoms correlate robustly with poorer quality of life after adjustment for depression (42). More than 58% of dialysis patients experienced chronic pain, and, of these, half rated the pain as moderate to severe (43). It would be instructive and sobering to know how many years patients like these survive with pain.…”
Section: Modality Choice In Practicementioning
confidence: 99%
“…Dialysis patients experience a high symptom burden for years, similar to that of patients with terminal cancer receiving palliative care (41,42), and symptoms correlate robustly with poorer quality of life after adjustment for depression (42). More than 58% of dialysis patients experienced chronic pain, and, of these, half rated the pain as moderate to severe (43). It would be instructive and sobering to know how many years patients like these survive with pain.…”
Section: Modality Choice In Practicementioning
confidence: 99%
“…Estudiosos ressaltam a importância do conhecimento do profissional de saúde, inclusive do enfermeiro, para uma melhor assistência, reduzindo danos e incapacidades e promovendo a qualidade de vida de pacientes em fases de adaptação e reabilitação (19) . (20) . Percebe-se, assim, que várias características definidoras estão presentes na clientela renal crônica em hemodiálise.…”
Section: Resultsunclassified
“…A substantial body of literature has shown that .58% of dialysis patients report pain, and 49% of these patients rate their pain as moderate or severe (1). However, surprisingly little is known about the prevalence and nature of chronic pain in patients with earlier stages of CKD.…”
mentioning
confidence: 99%
“…Chronic pain is associated strongly with considerable disability, lower health-related quality of life (HRQL), and burden to the healthcare system (1,6,7). The nephrology community has recognized this and has begun to advocate for routine screening and management of pain as a way to promote patient-centered, outcome-oriented, quality health care.…”
mentioning
confidence: 99%
See 1 more Smart Citation